2018
DOI: 10.14202/vetworld.2018.332-341
|View full text |Cite
|
Sign up to set email alerts
|

Status of theileriosis among herbivores in Iran: A systematic review and meta-analysis

Abstract: Aim:Theileriosis is a protozoal disease caused by Theileria spp. mostly in warm-blooded vertebrates worldwide. It is one of the common tick-borne diseases among domestic animals in tropical and sub-tropical regions, which have a variety of unlikable effects on health economy and animal welfare. In the present study, the prevalence of theileriosis among domestic farm animals in Iran was systematically evaluated.Methods:To identify the related papers, 10 English and Persian databases, including PubMed, Science D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The pooled estimates for theileriosis prevalence was 20% [95% level, CI 16-25%, PI 2-74%] in India and no studies with meta-analysis are available for comparison. However, a lower theileriosis prevalence of 14% was reported in cattle from Iran based on a meta-analysis (Soosaraei et al 2018). The prevalence of theileriosis was higher when compared to other tick-borne diseases namely, anaplasmosis [11%] prevalence by meta-analysis (Krishnamoorthy et al 2019a) and lower in comparison to Babesiosis [29%] in the World by meta-analysis (Jacob et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimates for theileriosis prevalence was 20% [95% level, CI 16-25%, PI 2-74%] in India and no studies with meta-analysis are available for comparison. However, a lower theileriosis prevalence of 14% was reported in cattle from Iran based on a meta-analysis (Soosaraei et al 2018). The prevalence of theileriosis was higher when compared to other tick-borne diseases namely, anaplasmosis [11%] prevalence by meta-analysis (Krishnamoorthy et al 2019a) and lower in comparison to Babesiosis [29%] in the World by meta-analysis (Jacob et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Among the species of Theileria, the most virulent and the main cause of fatal disease is T. piroplasms can be di cult to diagnose through direct examination and on the other hand, morphologically, they are very similar to microscopy, so they can be distinguished from each other using serological and molecular methods. (Soosaraei et al 2018). In the present study, we used peripheral blood smear and molecular methods for detection of Theileria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Mazandaran and Golestan are endemic for Babesia and Theileria vectors, and the livestock industry is a common tradition, accounting for roughly half of the industrial in this regions. In some of the world and in different parts of Iran, T. lestoquardi is considered as a main causal agent of theileriosis in small ruminants (Shayan and Rahbari 2007;Soosaraei et al 2018;GohNgugi et al 2016;LeemansBrown et al 1999;Razmi and Yaghfoori 2013). While some studies found T. ovis to be more prevalent than T. Lestoquardi, they also found mixed infection in 3% of cases and explained the main role of Theileria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Theileriosis is a tropical disease caused by obligate intracellular haemoprotozoa of Theileria genus that infect both leukocytes and erythrocytes and are transmitted by hard tick genera, mainly Amblyomma, Haemaphysalis, Hyalomma, and Rhipicephalus [177]. Wild and domestic ruminants are the main hosts in which infections cause enlargement of the lymph nodes, fever, anaemia, jaundice, leukopaenia, pulmonary oedema, lethargy, thrombocytopenia, and death [178].…”
Section: Theileriosismentioning
confidence: 99%